A Vanishing Left Ventricular Outflow Tract Mass: An Uncommon Manifestation of Systemic Lupus Erythematosus. Issue 7 (25th March 2014) - Ananthakrishna, Rajiv; Moorthy, Nagaraja; Bhat, Prabhavathi; Nanjappa, Manjunath C
Mini‐Abstract A 27‐year‐old female with a history of second trimester abortion was referred for evaluation of transient ischemic attack. Echocardiography revealed a large, irregular, mobile mass attached to the right coronary cusp of aortic valve. Investigations were consistent with antiphospholipid antibody syndrome, secondary to systemic lupus erythematosus. She was started on oral anticoagulation. Serial echocardiography showed regression of the mass, with complete resolution at 2 months. We highlight an uncommon manifestation of systemic lupus erythematosus, in the setting of a prothrombotic milieu. Prompt recognition is essential for appropriate therapy and averts the need for surgery.